Legal Construction of E-Notary Based on Discretionary Authority of Notaries - Utomo, Hatta Isnaini Wahyu (JURNAL AKTA, 2025)
In the 5.0 era, which is supported by the birth of new habits after the Covid-19 pandemic, which has accustomed people to activities using cyber technology. makes demands on Notaries to be able to adapt their services in making authentic deeds using cyber technology or what is known as e-Notary. Currently, e-Notary is difficult to implement because it is considered that there is no legal basis. This research analyzes the legal construction of the application of e-Notary based on the discretionary authority of the Notary and the application of e-Notary in context Ius Constitutum. This research is normative legal research using a statutory approach and a conceptual approach. The research results show that Notaries are part of public services. A notary is an official who carries out government functions to meet the needs of the public who need authentic deeds. Notaries are Government Officials so Notaries can use their Discretionary authority to carry out e-Notary. e-Notary can be implemented at this time by reinterpreting the provisions of Article 1868 of the Civil Code and the procedures for making authentic deeds as regulated in the Notary Position Law. The implementation of e-notary represents an adaption of the notary role in the digital age. The advantageous aspect of e-notary implementation is the convenience it offers the public in engaging with a notary for the creation of authentic deeds.